Effect of Pt-Ni/C Catalyst Composition Prepared via Impregnation-Ball Milling on Electrochemical Performance and Hydrogen Production in PEMWE - Novia Widia Ningsih; Dedi Rohendi; Addy Rachmat; Ady Mara; Muharni Muharni; Nyimas Febrika Sya'baniah; Dwi Hawa Yulianti; Diana Oktarina; Salsabilla Nabigha; Yollanda Nurcholifah (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2026)
This study investigates the effect of Pt–Ni/C catalyst composition prepared via impregnation and ball milling on electrochemical performance and hydrogen production in Proton Exchange Membrane Water Electrolysis (PEMWE). Five Pt:Ni ratios (1:0, 3:1, 1:1, 1:3, and 0:1) were evaluated using Linear Sweep Voltammetry (LSV), Cyclic Voltammetry (CV), Electrochemical Impedance Spectroscopy (EIS), and hydrogen production tests at 0.5–2.5 A. The Pt-rich catalyst (1:0) exhibited the highest intrinsic activity, with the largest charge (16.03 × 10^-3 C) and electrochemically active surface area (4.90 m2/g), while the 3:1 composition showed the lowest charge transfer resistance. The 1:1 composition achieved the best hydrogen production performance at 2.9 mL/s under 1.5 A, with stable behavior across varying current conditions, indicating a synergistic Pt–Ni interaction that enhances catalytic efficiency. These findings establish a direct correlation between electrochemical characteristics and hydrogen production performance, demonstrating that optimal catalyst performance is governed by a balance between intrinsic activity, charge transfer properties, and active site availability. The Pt–Ni/C (1:1) catalyst represents a promising strategy for designing cost-effective electrocatalysts for PEMWE applications.Keywords: Pt–Ni/C; impregnation; ball milling; PEMWE; hydrogen evolution reaction